Novel MOFs@XC-72-Nafion nanohybrid modified glassy carbon electrode for the sensitive determination of melamine. (1st September 2016) - Zhang, Wanqing; Xu, Guangri; Liu, Runqiang; Chen, Jun; Li, Xiaobo; Zhang, Yadong; Zhang, Yuping
Highlights: The MIL-53@XC-72 nanohybrid was synthesized from MIL-53 and followed by adulterating with XC-72. The synergistic effect of MIL-53 and XC-72 had promoted sensitivity and selectivity of the sensor. The reaction mechanism of melamine at sensors was explained. Abstract: A sensitive and selective sensor was fabricated to determine melamine (Mel), based on MIL-53@XC-72 nanohybrid modified glassy carbon electrode (GCE). The MIL-53@XC-72 nanohybrid was synthesized from MIL-53 via hydrothermal method, followed by adulterating with XC-72. The prepared sensor possessed high sensitivity and selectivity due to the synergistic effect of the large surface of MIL-53, the bonding interaction between Mel and MIL-53 as well as the high conductivity of XC-72. Under the optimal conditions, the sensor exhibited rapid electrochemical response to Mel at the potential of 0.7 V in 0.1 M HCl solution. A linear concentration range of Mel was obtained from 0.04 to 10 μM with a linear correlation coefficient of 0.998 and detection limit of 0.005 μM (S/N = 3). In addition, the sensor presented excellent reproducibility, high stability and selectivity, and was successfully applied for the determination of Mel in liquid milk with a good recoveries. Hence, the MOFs@XC-72-Nafion-GCE sensor could be considered as promising applicability for the determination of other electrochemically inactive analytes.